Should Feminists Forget Foucault? - Dominique D. Fisher (Studies in 20th & 21st Century Literature, 1998)
Up Against Foucault (1993), a collection of essays edited by Caroline Ramazanoglu, reevaluates Michel Foucault's theories on power and sexuality in regard to feminism from a sociological perspective…
Keywords: Up Against Foucault; Caroline Ramazanoglu; Michel Foucault; theories; power and sexuality; power; sexuality; feminism; sociological perspective; forget